DOI: 10.3990/1.9789036538626
|View full text |Cite
|
Sign up to set email alerts
|

Reforming the power : an institutional analysis of power sector reforms in Pakistan

Abstract: No part of this publication may be reproduced, stored in a retrieval system, or transmitted, in any form or by any means, electronic, mechanical, photocopying, recording or otherwise, without prior written permission of the author. [iv] [v]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 86 publications
(141 reference statements)
1
4
0
Order By: Relevance
“…The outcome does not support the laissez-faire theory that the market-oriented reforms improve the financial condition of both the sector and governments as they contribute towards achieving efficient pricing of electric service. Tanzania's experience seems to confirm earlier findings (Ullah, 2015) that developing countries that only opted for IPPs without divestiture faced difficulties in improving their overall financial condition. Cooksey (2017) claims that since 2002 when IPTL came on stream TANESCO has remained in a chronic insolvency situation as it has been paying more to IPPs and EPPs than it can charge the customers.…”
Section: Reforms and Liquiditysupporting
confidence: 77%
See 3 more Smart Citations
“…The outcome does not support the laissez-faire theory that the market-oriented reforms improve the financial condition of both the sector and governments as they contribute towards achieving efficient pricing of electric service. Tanzania's experience seems to confirm earlier findings (Ullah, 2015) that developing countries that only opted for IPPs without divestiture faced difficulties in improving their overall financial condition. Cooksey (2017) claims that since 2002 when IPTL came on stream TANESCO has remained in a chronic insolvency situation as it has been paying more to IPPs and EPPs than it can charge the customers.…”
Section: Reforms and Liquiditysupporting
confidence: 77%
“…Victor (2005) thus confesses that privatization does not make the sector profitable but generates early income to cash broke governments. On the other hand, Ullah (2015) observed that developing countries that only opted for IPPs without divestiture faced difficulties in improving their overall financial condition. Using data from 49 developing countries, the World Bank (2016) saw that after the reforms the cost recovery did not improve.…”
Section: Figure 1 Financial Viability Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ltd. This led to the launch of a motorcycle manufacturing factory at the Bin Qasim Industrial Park Karachi in 2015 with approximately 1,400 employees and a production target of 400,000 units by the end of 2020 (Ullah, 2015). Yamaha Motor Pakistan (Pvt.)…”
Section: Case Study Descriptionmentioning
confidence: 99%